China's climate change policies - Wang, Weiguang, 1950-; Zheng, Guoguang; Pan, Jiahua (Routledge, 2012)
"At the end of 2010 in the coast city, Cancun, Mexico, the United Nations Framework Convention on Climate Change (UNFCCC) convened its 16th Conference of the Parties (COP16), which received another round of great attention from the whole world. This book calls together experienced experts with in-depth understanding on scientific assessment of climate change and relevant social and economic policies and senior experts who directly participate in the international climate negotiations. This will help the readers to better understand the upcoming Durban conference, as well as China's long-term strategy in response to climate change. This book includes researches on China's 12th Five year plan; pilot low carbon city actions; policies and pathways for China's national appropriate mitigation actions; China's forestry management; China's NGOs and climate change; low carbon expo in Shanghai China 2010; Carbon budget proposal; China's green economy and green jobs; China's reaction to carbon tariff; China's actions in adaptation approaches; China's accumulative carbon emissions, etc. This gives the readers a comprehensive understanding of the latest developments of China's actions in response to climate change, the results of these actions, and the challenges that are still being faced. China is becoming a raising star in global economical and political affairs. Both international society and China itself have great expectation to its future role. This book clarifies China's leading position in many aspects. However, limited to its development stage, natural resource endowment, and other unbalanced developing issues, China is still a developing country. This book reveals a real China to the audience, which can provide a more comprehensive solution to future global climate regime"--